2017
DOI: 10.3390/molecules22111912
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Study of Copper-Catalyzed C-H Hydroxylation/C-S Coupling by ESI-HR MS and DFT Calculations

Abstract: The reaction mechanism of Cu-catalyzed C-H hydroxylation/C-S coupling was studied using electrospray ionization high resolution mass spectrometry (ESI-HR MS) and density functional theory calculations (DFT). Notably, a series of CuI and CuIII complexes were observed as key intermediates and identified using ESI-HR MS. Furthermore, a catalyst cycle involving proton abstraction/oxidative addition/reductive elimination was proposed. This study is important and valuable with respect to C-H functionalization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 42 publications
(38 reference statements)
2
5
0
Order By: Relevance
“…2,7] and similar to the data indicated by [1] in jerboa and by [7] in dogs, their quantity was less in the superficial region of the cortical labyrinth than that of the of mid-cortical and juxtamedullary regions[ Fig.2,6]. The study of [19] in the kidney of the Bactrian camel recorded that renal corpuscles were absent below the capsule in the range of 1000 to 1500 μm while in the current work we observed some of the renal corpuscles are present directly below the capsule in the hilar region [ Fig. 1B].…”
Section: Bowman's Capsule and Glomerulussupporting
confidence: 74%
See 3 more Smart Citations
“…2,7] and similar to the data indicated by [1] in jerboa and by [7] in dogs, their quantity was less in the superficial region of the cortical labyrinth than that of the of mid-cortical and juxtamedullary regions[ Fig.2,6]. The study of [19] in the kidney of the Bactrian camel recorded that renal corpuscles were absent below the capsule in the range of 1000 to 1500 μm while in the current work we observed some of the renal corpuscles are present directly below the capsule in the hilar region [ Fig. 1B].…”
Section: Bowman's Capsule and Glomerulussupporting
confidence: 74%
“…Numerous sections of thin segments of Henle's loops were seen in the inner medulla zone of the kidney and this indicated that there were many nephrons with long loops are present in the kidney of a weasel which were a prerequisite for the production more concentrated urine in the arid and semi-arid environments. A similar observation was recorded by [13] in long-eared hedgehogs and by [19] in Bactrian camel. The thick segments of the loop of Henle had clear circular lumina, lined by one layer of low cuboidal cells [ Fig.8] which was similar to that recorded by [17] in Marwari sheep and by [3] in albino rats.…”
Section: Loop Of Henlesupporting
confidence: 68%
See 2 more Smart Citations
“…71 Another study by the same group revealed that Sal B is capable to inhibit ET-1 and thereby reduces the contraction of primary rat HSCs through its suppressive effects on myosin light chain 2 phosphorylation in HSCs. 72…”
Section: Modulators Of Et-1 Signaling and Portal Hypertensionmentioning
confidence: 99%